2022
DOI: 10.3176/oil.2022.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the hydrocarbon generation of low maturity organic-rich shale in supercritical water

et al.

Abstract: In this study, the hydrocarbon generation of 1-4 cm sized shale in supercritical water (SCW) was investigated. The results showed that temperature was the most important factor affecting the hydrocarbon generation of organic-rich shale in the presence of supercritical water. In the temperature range of 380-450 °C, the optimum oil generation temperature was 430 °C. The produced oil component became heavier with increasing temperature. Increasing temperature was beneficial to gas production and improved the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…SCW has a stronger ability to dissolve organic compounds. Xie studied the hydrocarbon generation efficiency and pyrolysis products of organic-rich shale under SCW and effectively concluded insights into the mechanism of SCW in favor of organic carbon utilization. , Wang studied the effects of different extraction conditions on pyrolysis products using isothermal subcritical water extraction technology and concluded that subcritical water possessed the effects of catalytic pyrolysis and extraction solvent . Pyrolysis kinetics is also an effective analytic method to investigate shale pyrolysis behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…SCW has a stronger ability to dissolve organic compounds. Xie studied the hydrocarbon generation efficiency and pyrolysis products of organic-rich shale under SCW and effectively concluded insights into the mechanism of SCW in favor of organic carbon utilization. , Wang studied the effects of different extraction conditions on pyrolysis products using isothermal subcritical water extraction technology and concluded that subcritical water possessed the effects of catalytic pyrolysis and extraction solvent . Pyrolysis kinetics is also an effective analytic method to investigate shale pyrolysis behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the technology of hydrocarbon generation from medium- and low-maturity organic-rich shale in supercritical water conversion has been given much attention. The thermal degradation of medium- and low-maturity organic-rich shale to produce hydrocarbon is a complex physicochemical process, which results in a wide variety of products, which makes it difficult to determine the kinetic law and mechanism of pyrolysis. In addition, supercritical water was introduced into the transformation of medium- and low-maturity organic-rich shale to generate hydrocarbons, which undoubtedly made the pyrolysis process more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Low maturity organic-rich shale (LMOS) is an important part of oil shale resources, and its material composition mainly includes inorganic minerals, a large amount of solid kerogen, and a small number of mobile hydrocarbons. , The bottleneck of its effective development lies in how to accelerate the production of oil and gas from kerogen. , For this reason, people put forward a lot of heat conversion technologies as the core, such as electric heating technology, fluid heating technology, radiation heating technology, combustion heating technology, and so on . Among them, fluid heating technology uses the heat transfer mode of heat convection and conduction, which has the advantages of high heating efficiency and supplement of reservoir driving energy.…”
Section: Introductionmentioning
confidence: 99%